QIBLAT TIAP SAAT SEBAGAI JEMBATAN PENENTU ARAH QIBLAT - Sayful Mujab (Program Studi Hukum Keluarga Islam, 2015)
There are several methods to determine the direction of Qibla. Theories commonly taught to the stu dents of College of Islamic Studies are (1) the theory of qibla direction, (2) the theory of qibla shadows or commonly referred to roshdul qibla, and (3) the theory of anytime qibla. The application of each theory depends on the time. For example, using istiwa’ stick, people need to look at the shadow of the sun in the morning and the evening to draw a line from east to west to determine the direction of qibla. Using rashdul qibla, people have to wait for annual sun shadow, on 27/28 May and 15/16 July each year. On that day, the sun is right above Kaaba. There is also daily rashdul qibla when the sun or its shadow is in the same direction with Kaaba. The third method is anytime qibla by calculating the azimuth of the sun, the direction or its shadow to determine the qibla. Compare to the first two methods, the third one is more applicable.